Characterization of the molecular genetic pathology in patients with 11β‐hydroxylase deficiency. (14th July 2015) - Mooij, Christiaan F.; Parajes, Silvia; Rose, Ian T.; Taylor, Angela E.; Bayraktaroglu, Taner; Wass, John A.H.; Connell, John M.C.; Ray, David W.; Arlt, Wiebke; Krone, Nils
Summary Objective Steroid 11β‐hydroxylase (CYP11B1) deficiency (11OHD) is the second most common form of congenital adrenal hyperplasia. Nonclassic or mild 11OHD appears to be a rare condition. Our study assessed the residual CYP11B1 function of detected mutations, adding to the spectrum of mild 11OHD, and illustrates the variability of the clinical presentation of 11OHD. Patients and methods Five patients presented with mild to moderate 11OHD. Two women presented with mild hirsutism and in one case with secondary amenorrhoea. Two men presented with precocious pseudopuberty, gynaecomastia and elevated blood pressure. One 46, XX female patient was diagnosed with virilization of the external genitalia 2 years after birth. Direct DNA sequencing was carried out to perform CYP11B1 mutation analysis. The CYP11B1 mutations were functionally characterized using an in vitro expression system. Results CYP11B1‐inactivating mutations were detected in all patients. Two novel missense mutations (p.P42L and p.A297V) and the previously characterized p.R143W mutation had residual CYP11B1 activities between 10% and 27%. A novel p.L382R and the previously uncharacterized p.G444D mutation both caused complete loss of CYP11B1 enzymatic activity. Conclusion Mutations causing partial impairment of 11β‐hydroxylase activity (residual activity of 10% or above) are associated with a less severe clinical presentation of 11OHD, which can be classified as a nonclassic form. Our data demonstrate that patients with nonclassic 11OHD can present with androgen excess, precocious pseudopuberty and increased blood pressure. Timely diagnosis of nonclassic 11OHD and consequently initiation of personalized treatment is essential to prevent co‐morbidities caused by androgen excess and hypertension.